Peran Guru BK dalam Meningkatkan Keaktifan Siswa Tunarungu pada Ekstrakurikuler Kerajinan di SMP Negeri 7 Samarinda - Suci Karomah; Rury Muslifar (Panthera : Jurnal Ilmiah Pendidikan Sains dan Terapan, 2026)
This study aims to describe the role of Guidance and Counseling teachers (BK) in increasing the activeness of deaf students in craft extracurricular activities at SMP Negeri 7 Samarinda. This study uses a qualitative approach with a descriptive method. The research subjects consisted of three BK teachers, one Cultural Arts Teacher, and two deaf students. Data collection techniques use interviews, observations, and documentation. The results of the study show that BK teachers have an important role as motivators, directors, facilitators, initiators, mediators, evaluators, informers, and organizers in increasing the activeness of deaf students. Through planned tutoring and ongoing support, deaf students show an increase in confidence, independence, and active participation in craft activities. These findings confirm that the role of BK teachers does not only focus on individual counseling aspects, but also includes social empowerment and strengthening the independence of students with special needs in an inclusive school environment.